Environmentally friendly landscape management improves oilseed rape yields by increasing pollinators and reducing pests. Issue 7 (24th May 2022) - Perrot, Thomas; Bretagnolle, Vincent; Gaba, Sabrina
Abstract: Pollination and pest control are two major ecological functions sustaining crop yield. In insect‐pollinated crops, previous studies have revealed that an increase in resources and habitats in landscapes can increase pest control by natural enemies as well as insect pollination by pollinators. However, data have been lacking that simultaneously considers the effects of landscape on both pollinators and pests, and the direct and indirect effects on yields of farming practices interacting with landscape, bees and pests. This study aimed to fill this gap by focusing on oilseed rape (OSR), an insect‐pollinated crop of high economic value. We first quantified the effects of landscape and farming practices on both bee and pest abundance caught in OSR blooming season in 124 farmed fields over a 6‐year study ( 20 fields sampled per year), and then used structural equation modelling to assess the direct and indirect links between bees, pests, farming practices and landscape on yield. The results showed that landscape had a stronger effect on bee and pest abundance than agrochemical farming practices. Bees and pests decreased with the amount of OSR in the landscape surrounding the focal field, and showed contrasted effects with the amount of meadow and organic farming: positive for bees and negative for pests. Bee abundance also increased with the amount of sunflower in the landscape the preceding year, and decreased with increasing field size. While agrochemicals surprisingly had barely any effect on bees and pests, their use improved OSR yield, although at a similar magnitude as bee and pest abundances. Synthesis and application . This study, conducted in commercial crop fields, underlines the important contribution of sustainable landscape management for enhancing OSR yield. Despite agrochemicals' ability to improve or maintain OSR yields, their unconditional use is unsustainable due to negative externalities. Therefore, alternative options such as those highlighted in our study—such as reducing field size, increasing the amount of organic farming in the landscape, or sowing OSR in landscapes rich in sunflowers the preceding year—appear to be relevant tools to promote ecosystem services, maintain yield and conserve biodiversity. These findings support the potential of nature‐based solutions to foster more sustainable agriculture. Abstract : This study, conducted in commercial crop fields, underlines the important contribution of sustainable landscape management for enhancing OSR yield. Despite agrochemicals' ability to improve or maintain OSR yields, their unconditional use is unsustainable due to negative externalities. Therefore, alternative options such as those highlighted in our study—such as reducing field size, increasing the amount of organic farming in the landscape or sowing OSR in landscapes rich in sunflowers the preceding year—appear to be relevant tools to promote ecosystem services, maintain yield and conserve biodiversity. These findings support the potential of nature‐based solutions to foster more sustainable agriculture. Résumé: La pollinisation entomophile et la régulation naturelle des ravageurs par les ennemis naturels sont deux fonctions écologiques majeures qui affectent les rendements des cultures. L' augmentation des ressources et des habitats dans les paysages agricoles augmente le contrôle des ravageurs par les ennemis naturels ainsi que la pollinisation par les pollinisateurs. Or ces études ont été menées séparément, limitant notre capacité de proposer des stratégies de gestion de paysage favorisant simultanément les pollinisateurs et les ravageurs. Nous disposons également de peu d'information pour comprendre comment le paysage les pratiques agricoles, les abeilles et les ravageurs interagissent dans l'élaboration du rendement. Cette étude visait à combler cette lacune en se concentrant sur le colza, une culture dépendante des insectes et d'importance économique forte pour les agriculteurs. Dans un premier temps, nous avons quantifié les effets du paysage et des pratiques agricoles sur l'abondance des abeilles et des ravageurs capturés pendant la saison de floraison du colza dans 124 parcelles cultivées par des agriculteurs au cours d'une étude de six ans ( 20 parcelles échantillonnées par an). Ensuite, nous avons construit un modèle d'équation structurelle pour évaluer les liens directs et indirects entre les abeilles, les ravageurs, les pratiques agricoles et le paysage sur le rendement. Les résultats révèlent que le paysage a un effet plus important sur l'abondance des abeilles et des ravageurs que les pratiques agricoles en particulier les fertilisants et les pesticides. L'abondance des abeilles et des ravageurs diminuent avec la quantité de colza dans le paysage autour des parcelles étudiées, mais répondent différemment à la quantité de prairie et de parcelles en agriculture biologique: positifs pour les abeilles et négatifs pour les ravageurs. L'abondance des abeilles augmente également avec la quantité de tournesol dans le paysage l'année précédente, et diminue avec l'augmentation de la taille des parcelles. Alors qu'étonnamment presque aucun effet des fertilisants et des pesticides n'a été détecté sur les abeilles et les ravageurs, leur utilisation permet d'obtenir des rendements de colza plus important, à un niveau similaire à celui de l'effet des abondances d'abeilles et des ravageurs. Synthèse et application . Cette étude, menée directement dans les parcelles des agriculteurs, souligne l'importante d'une gestion durable du paysage pour augmenter ou maintenir les rendements du colza. Des alternatives aux fertilisants et aux pesticides telles que celles mises en évidence dans notre étude ‐ comme réduire la taille des parcelles, augmenter la quantité d'agriculture biologique dans le paysage, ou cultiver du colza dans des paysages riches en tournesol l'année précédente ‐ semblent être des leviers efficaces pour promouvoir l'expression de services écosystémiques permettant de concilier production agricole et conservation de la biodiversité. Ces résultats confirment le potentiel des solutions fondées sur la nature pour favoriser une agriculture plus durable.